PROMOCIÓN TURÍSTICA Y SU IMPACTO EN EL CRECIMIENTO ECONÓMICO DEL CENTRO RECREACIONAL HACIENDA SAN FRANCISCO DEL CANTÓN BUENA FE, AÑO 2022 - Rodríguez Narváez, Ariana Maithe (2022)
Tourism has become one of the main players in trade and a major source of income for many developing countries. This growth goes hand in hand with increasing diversification and competition between destinations. This research or dissertation is carried out prior to obtaining the degree in Hospitality and Tourism, its purpose is to analyze tourism promotion and its impact on the economic growth of the hacienda San Francisco Recreational Center in the Buena Fe canton, year 2022. The objective is analyze the factors that determine the tourist promotion of the Hacienda San Francisco tourist center since it is a natural area that has a history, culture and in it the crossing of a natural river which makes tourism develop. The applied methodology has been bibliographical research, field research, descriptive research and analytical research, which was able to collect information in a macro and micro way, the description of tourism that takes place in the canton of Buena Fe contributing to tourism development and economic stability, whose results showed that most of the inhabitants do know the recreational center and it is visited by people of all ages, either for recreation or work.